Cytisine induced urticaria : a case report during a smoking cessation treatment - Campagnari, Simone; Casari, Rebecca; Zamboni, Lorenzo; Lugoboni, Fabio (Acta Biomedica Atenei Parmensis, 2022)
Cytisine is considered to be the oldest medication for smoking cessation and has been used for this purpose in some Eastern/Central European and Central Asian countries for over 50 years.Several sources points towards cytisine’s efficacy and effectiveness; it’s well tolerated when taken at the recommended dose, and adverse events reported in trials are typically non-serious and self-limiting gastrointestinal and sleep disturbances.We report a suspect case of urticaria during treatment for smoking cessation with cytisine in a woman of 48 years treated for smoking at the Unit of Addiction Medicine, Department of Internal Medicine, Hospital Trust of Verona, Italy. The therapeutic protocol of cytisine that was used is of the "inductive" type; it consists in gradually increasing the daily capsules taken, with a parallel reduction in the number of cigarettes smoked until complete cessation between the fifth and ninth day of therapy (quit day) The number of capsules taken is then gradually reduced.She was treated for the firsts three days with betamethasone 1 mg/die, on the advice of her general practitioner, and suspended Cytisine. A week later the patient showed signs of recovery.